2000
DOI: 10.1076/1380-3395(200002)22:1;1-8;ft080
|View full text |Cite
|
Sign up to set email alerts
|

Demographically Corrected Norms for the California Verbal Learning Test

Abstract: The California Verbal Learning Test (CVLT) is designed to quantify components of verbal learning, retention and retrieval. The present study used multiple regression analyses to correct for demographic characteristics on CVLT performance measures. There were 906 subjects, of whom 549 were Caucasians (61%) and 357 were African Americans (39%). Age, education, ethnicity, and gender were found to be significant predictors of performance on several CVLT indices, including Total Words Recalled, Trial 1, Trial 5, Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
89
2
10

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(113 citation statements)
references
References 9 publications
12
89
2
10
Order By: Relevance
“…In general, the higher the education the more words were recalled. Similar results have been reported for word recall tasks (Donders, 2008;Messinis, Tsakona, Malefaki, & Papathanasopoulos, 2007;Norman, Evans, Miller, & Heaton, 2000;Teruya, Ortiz, & Minett, 2009).…”
Section: Discussionsupporting
confidence: 76%
“…In general, the higher the education the more words were recalled. Similar results have been reported for word recall tasks (Donders, 2008;Messinis, Tsakona, Malefaki, & Papathanasopoulos, 2007;Norman, Evans, Miller, & Heaton, 2000;Teruya, Ortiz, & Minett, 2009).…”
Section: Discussionsupporting
confidence: 76%
“…It has also led to studying variables that are proxies for ethnicity but are more precisely related to culture, education, and access. Comparing the performance of racial0 ethnic minorities to demographically similar groups has led to decreases in misclassification rates (Lucas et al, 1998;Norman et al, 2000;Heaton et al, 2001;Patton et al, 2003), which is a primary benefit of norms that account for ethnicity (Manly, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have reported a significant positive relationship between years of education and performance on cognitive measures including word recall tasks (e.g., Anstey & Christensen, 2000) with those individuals with more years of education performing better on measures of cognition than those with less education. Two studies have reported found a significant positive association between years of education and recall performance on the AVLT (Query & Megran, 1983;Uchiyama et al, 1995; see also Norman et al, 2000). Prior studies have not examined the extent to which health is associated with initial recall or growth; however, various indices of health and disease are associated with memory performance (Hultsch, Hammer, & Small, 1993;Verhaeghen, Marcoen, & Goossens, 1992).…”
mentioning
confidence: 99%
“…In addition, gender has been associated with the magnitude of learning gains over five trials of the CVLT, with females exhibiting greater gains than males (Lamar et al, 2003). Norman, Evans, Miller, and Heaton (2000) found differences in the CVLT between African American and white older adults in initial recall and overall performance (see also Uchiyama et al, 1995). A number of studies have reported a significant positive relationship between years of education and performance on cognitive measures including word recall tasks (e.g., Anstey & Christensen, 2000) with those individuals with more years of education performing better on measures of cognition than those with less education.…”
mentioning
confidence: 99%